Abundant and rare microbial sub-communities in anammox granules present contrasting assemblage patterns and metabolic functions in response to inorganic carbon stresses. (October 2018) - Shu, Duntao; Zhang, Baogang; He, Yanling; Wei, Gehong
Graphical abstract: Highlights: Abundant and rare taxa present divergent assemblage patterns and functional traits. Functional traits dominated the selection of bacterial sub-communities. Abundant taxa was the key regulator for NH4 + -N and NO2 − -N consumption. NH4 + -N and NO2 − -N accumulation was mediated by the rare sub-community. Nitrogen conversion pathways were mediated by different bacterial sub-communities. Abstract: Nitrogen-transforming microorganisms play pivotal roles for the microbial nitrogen-cycling network in the anammox granular system. However, little is known about the effects of inorganic carbon (IC) stresses on the assemblage patterns and functional profiles of abundant and rare taxa. Herein, the community assemblage and functional traits of abundant and rare sub-communities were investigated. Results revealed that insufficient IC had adverse influences on the process performance, while anammox activity could be recovered by IC addition. Co-occurrence network analysis indicated that abundant and rare sub-communities present divergent co-occurrence patterns. Additionally, environmental filtering had different influences on the ecological adaptability of bacterial sub-communities. Furthermore, qPCR results illustrated that NH4 + -N and NO2 − -N consumption were regulated by abundant sub-community, while their accumulation was mediated by rare sub-community. Collectively, these findings suggest that abundant and rare sub-communities present contrasting assemblage patterns and metabolic pathways, and functional profiles dominated selection of bacterial sub-communities under IC stresses.